2011
DOI: 10.1016/j.eurpsy.2010.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ subjective initial response and the outcome of inpatient and day hospital treatment

Abstract: Objective: This study aimed to establish whether psychiatric patients' subjective initial response (SIR) to hospital and day hospital treatment predicts outcomes over a one year follow-up period. Method:We analysed data from 765 patients who were randomised to acute psychiatric treatment in a hospital or day hospital. SIR was assessed on day three after admission. Outcomes were psychiatric symptom levels and social disability at discharge, and at 3 and 12 months after discharge. Results:After controlling for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…(Blais, ; Kerfoot, Bamford, & Jones, ; Rise, Eriksen, Grimstad, & Steinsbekk, ). Consumers also assessed satisfaction with care poorly (CAT mean 5.5) compared with other studies (Priebe et al., , ), although similar to previous findings of an involuntary inpatient population (Priebe et al., ). Compared with population norms for females aged between 12‐42 (Carter, Stewart, & Fairburn, ; Mond, Hay, Rodgers, & Owen, ), the consumers surveyed for this study reported severe eating disorder psychopathology across all subscales, well above the community norms for Global EDE‐Q scores of between 1.5‐1.6.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…(Blais, ; Kerfoot, Bamford, & Jones, ; Rise, Eriksen, Grimstad, & Steinsbekk, ). Consumers also assessed satisfaction with care poorly (CAT mean 5.5) compared with other studies (Priebe et al., , ), although similar to previous findings of an involuntary inpatient population (Priebe et al., ). Compared with population norms for females aged between 12‐42 (Carter, Stewart, & Fairburn, ; Mond, Hay, Rodgers, & Owen, ), the consumers surveyed for this study reported severe eating disorder psychopathology across all subscales, well above the community norms for Global EDE‐Q scores of between 1.5‐1.6.…”
Section: Resultssupporting
confidence: 72%
“…Consumer satisfaction with care was measured with the Client Assessment of Treatment Scale (CAT) scale, consisting of seven items that are rated along a 10 point visual analogue scale (Priebe et al, 2009). The scale has been used in several inpatient mental health studies (Kallert et al, 2007;Priebe et al, 2006Priebe et al, , 2011Richardson et al, 2011). It has a good internal consistency (Cronbach's alpha = 0.90) (Priebe et al, 2009), factorial validity and consistency across samples (Richardson et al, 2011).…”
Section: The Client Assessment Of Treatment Scalementioning
confidence: 99%
“…The average duration of interviews was 40 min for nurses, 25 min for consumers. From phase one, it was established that consumers perceived a relatively poor therapeutic alliance with nurses (mean I‐TAS 3.70, SD 1.30) (Blais, ; Rise, Eriksen, Grimstad, & Steinsbekk, ), a low satisfaction with care (mean CAT 5.5, SD 2.33) (Priebe et al., , ) and a high degree of eating disorder pathology (mean global EDE‐Q 4.0, SD 1.49) (Carter, Stewart, & Fairburn, ; Mond, Hay, Rodgers, & Owen, ). Nurses reported a high quality of attitudes towards mental health consumers (mean ATAMHS‐33 sum of 185.6, SD 21.97) (Baker et al., ; Foster, Usher, Baker, Gadai, & Ali, ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, patient satisfaction predicts outcomes right from the initial stages of treatment, e.g. when assessed within the first two days of hospital care. It is also a quality indicator, because all treatments should be as patient friendly as possible, independently of any impact on health and social outcomes.…”
mentioning
confidence: 99%